Exploring the Trajectories of Myth, Truth, and Childhood in Mahasweta Devi’s The Armenian Champa Tree - Fatima, Jabeen (SARE: Southeast Asian Review of English, 2018)
The distinctiveness of Mahasweta Devi’s writings lies in their element of resistance. Given the celebration of her oeuvre as a body of serious activist writing, what is often overlooked is that Devi is also a writer of children’s fiction. This paper focuses on The Armenian Champa Tree (2000), one of her novellas written for a young readership. The narrative unravels those malevolent aspects of folk culture and social behavior that Devi believes are responsible for regression and self-defeat among individuals and families, especially those from the under-class, and the deleterious effects on children. The paper discusses the susceptibility of this key Indian demographic to rumors and mistruths and the author’s foregrounding of recuperative strategies that exist or could be brought into practice. The concern with witch-hunts, for example, is an urgent and pertinent one in a global context, given the rampant planned slaughters of individuals and families by vengeful parties on the pretext of purgation.